Incorporating Learning Styles to Motivate High School Students in Reading - Yokhebeth Yokhebeth (Kata Kita: Journal of Language, Literature, and Teaching, 2018)
In the high school where this research was done, the biggest problem for the students, when it comes to English tests, is the reading section. Because they do not like reading, their reading scores are low. Reflecting to this fact, the idea of learning styles was applied in the reading class to help the students like reading so that they understand the text better. This research used mainly the idea of Visual Auditory and Kinesthetic learning styles suggested by Neil Fleming in 1992. The research was done in a class of forty students with different levels of English proficiency. There were three sessions in which each session had different learning styles applied to the activities. The result of this research was as expected with some exceptions. Both the ones who have high and low level of English understand the reading texts better when the learning styles applied match with theirs. However, there were also special cases in which students got their highest scores in the sessions that did not match with their personal learning styles. One of the possibilities on why these special cases occurred is the possible existence of the secondary learning styles. Neil Fleming mentioned in one of his journals that it is possible for these learning styles to overlap - one person can have more than one learning style with one style as the dominant learning style